Effectiveness of Banana Peel Ash, Zeolite and Clam Shells in Reducing Waterturbidity and Iron (Fe) Contentration - Selviana, Selviana; Kamaran; Suwarni, Linda; Suharno (Gema Lingkungan Kesehatan, 2025)
One method to reduce iron content and water turbidity is to use banana peel coagulants and zeolite and clam shell filtration. The biochemical components in banana peels are believed to be effective in reducing turbidity and heavy metals, while zeolites and clam shells function to reduce iron levels in water. This study aims to determine the effectiveness of kepok banana peel ash coagulant (Musa acuminate balbisiana C.) and zeolite and clam shell filtration in reducing turbidity and iron (Fe) content in river water in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency. The research method used was a quasi-experiment with a one-group pretest-posttest design, taking river water samples in Punggur Kecil Village, as many as 27 samples from 9 repetitions. Data were analyzed descriptively with the paired sample t-test statistical test. The results of the analysis showed that river water treatment using banana peel ash coagulant and clam shell filtration and zeolite decreased the average iron (Fe) content from 2.21 mg/l to 0.25 mg/l, with an effectiveness of 88.18%, but there was no significant change. While the average decrease in turbidity levels was from 57.67 NTU to 17.6 NTU, with an effectiveness of 65.56%, the results were also not significant. The results of the paired t-test showed a significant difference before and after treatment in iron content with a value of 0.000 (p < 0.05) and turbidity content with a value of 0.003 (p < 0.05). The conclusion of this study shows a significant difference in iron (Fe) and turbidity levels, but this treatment method has not been effective in reducing the level of turbidity of river water. The conclusion of this study shows a significant difference in iron (Fe) and turbidity levels, but this treatment method has not been effective in reducing the level of turbidity of river water.